2019
DOI: 10.1097/md.0000000000016224
|View full text |Cite
|
Sign up to set email alerts
|

Lobar location of lesions in computed tomography-guided lung biopsy is correlated with major pneumothorax

Abstract: Pneumothorax is a common complication in computed tomography (CT)-guided percutaneous lung biopsy (CPLB). Whether the lobar location of lesions contributes to the incidence of pneumothorax should be further clarified. A total of 1452 consecutive patients who underwent CPLB between January 2010 and March 2018 were retrospectively analyzed. The incidence of pneumothorax was compared among 5 different lobe biopsies. Minor pneumothorax was defined as pneumothorax without chest tube placement and major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The histological type diagnosis of lung cancer is fundamental in guiding patient management. Lung biopsy is a well-established method for the differential diagnosis of lung lesions (7), but it is expensive and invasive. Lung Adenocarcinoma (Adc) is the most common subtype of lung cancer (8), and diagnosing Adc by biopsy is not beneficial to the patients unfit for the invasive diagnostic procedure.…”
Section: Introductionmentioning
confidence: 99%
“…The histological type diagnosis of lung cancer is fundamental in guiding patient management. Lung biopsy is a well-established method for the differential diagnosis of lung lesions (7), but it is expensive and invasive. Lung Adenocarcinoma (Adc) is the most common subtype of lung cancer (8), and diagnosing Adc by biopsy is not beneficial to the patients unfit for the invasive diagnostic procedure.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Previous literature indicated that when the targeted lesion located in the upper or middle lobe, major pneumothorax rate was often higher due to more punctures through fissure. 21 Hence, the operators should avoid traversing fissure as far as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Al analizar la ocurrencia de complicaciones respecto a la localización de las lesiones, se encontró que 7 de 17 pacientes con complicaciones (41,2 %) tenían la lesión en el lóbulo inferior derecho, lo que es coherente con estudios previos en los cuales se ha informado que las lesiones en el lóbulo inferior derecho y en el lóbulo medio presentan mayores tasas de complicación, con el neumotórax como la más frecuente (27).…”
Section: Discussionunclassified